A Case of Euthyroid Graves' Ophthalmopathy in a Patient Sero-Negative for TSH Receptor Autoantibody. (13th June 2018) - Hotta, Asami; Tanaka, Tomohiro; Kato, Haruka; Kakoi, Shota; Shimizu, Yuki; Hasegawa, Chie; Hayakawa, Akiko; Yasuda, Satoshi; Ogawa, Kento; Ito, Shunsuke; Ohguchi, Hideomi; Yagi, Takashi; et al.
Abstract : We report of a case of Graves' ophthalmopathy presented solely with symptoms of the eyes with normal thyroid function tests and negative immunoreactive TSH receptor autoantibody. 40-year-old male was referred to our hospital due to 2-month history of ocular focusing deficit without any signs or symptoms of hyper- or hypothyroidism. Serum thyroid function tests and 99 m Tc uptake were both within the normal range. Anti-thyroid autoantibodies were all negative except for the cell-based assay for serum TSH receptor stimulating activity. Since orbital CT scan and MRI gave typical results compatible with Graves' ophthalmopathy, we treated the patients with corticosteroid pulse therapy and orbital radiation therapy, leading to a partial improvement of the symptoms. This case gives insights into the potential pathophysiologic mechanism underlying Graves' ophthalmopathy and casts light upon the difficulties of establishing the diagnosis in a euthyroid case with minimal positive results for anti-thyroid autoantibodies.